Efektivitas Teknik Kultur menggunakan Sistem Kultur Statis, Semi-kontinyu, dan Kontinyu terhadap Produktivitas dan Kualitas Kultur Spirulina sp. - Gede Suantika; Deri Hendrawandi (Jurnal Matematika & Sains, 2009)
Cyanobacteria, Spirulina sp., is used in many industries such as aquaculture, medical, and food industry due to its high nutrient level such as protein, fatty acid, vitamin, and antioxidant. In this experiment, three different culture techniques of batch culture, semi-continuous culture, and continuous culture were tested and developed in order to evaluate their effects on Arthrospiras culture production. During 24 days of culture period, batch culture biomass produced was 6.53±0.16 g, semi-continuous culture was 7.51±0.22 g, and continuous culture was 5.42±0.02 g. The highest contaminant presence was obtained in continuous culture, the highest pH level was found in semi-continuous culture. The highest concentration of nitrate, nitrite, ammonium, and orthophosphate was measured in continuous culture. Based on the result, it can be concluded that semi-continuous culture can produce highest biomass for 24 days culture period with a total production of biomass was 7.51±0.22 g and can maintain the stability of water quality.